Construction Health and Safety: Effectiveness of Safety Incentive Programme - Zulkefli, F.A.; Md Ulang, N.; Baharum, F. (EDP Sciences, 2014)
Safety incentive programmes or awards have become a standard practice for most construction companies as an effort to improve their safety performance on worksites. Providing incentives in the construction industry is an action which aims to motivate contractors and workers to achieve the objectives set by a project’s management in order to improve overall performance on the project. This study was conducted to measure the effectiveness of such incentives and analyse the extent of involved parties’ contribution to the success of the programme. It was found that workers have become motivated and site safety performance has also improved since the implementation of the safety incentive programme. Incentives are divided into two categories, (1) monetary and (2) non-monetary. These were evaluated based on workers’ rate of achievement or behaviour.